Sporicidal activity mechanism of lactic acid and peracetic acid on bovine pathogenic Bacillus cereus spores - Zhang, Xin; Chen, Yunjiao; Zhao, Jingjing; Zheng, Haiying; Liu, Lanlan; Liu, Wei; Fu, Mingshan; Jia, Weijuan; Jia, Zelin; Cui, Jiayu; Zhang, Yuhang; Xiong, Huisheng; et al. (The Thai Journal of Veterinary Medicine, 2026)
In recent years, the pathogenicity of Bacillus cereus (B. cereus) has increased significantly, its host adaptability has continued to expand, and the infection spectrum has also expanded. At the same time, food contamination by B. cereus is also common. Therefore, it is of practical significance to select green, safe and effective inhibitors. Lactic acid (LA) and peroxyacetic acid (PAA) possess good antibacterial properties, making them environmentally friendly, safe, and non-toxic. The purpose of this experiment was to preliminarily explore the inhibition mechanism of LA and PAA on B. cereus spores. The effects of LA and PAA on B. cereus spores were evaluated by measuring the MIC and MBC of LA and PAA inhibiting B. cereus spores, the effect of spore germination, the turbidity of spore suspension (OD600), the release of macromolecules in spores, the content of ROS in spores, the release of DPA in spores and the hydrophobicity of spore surface. The results showed that the MIC and MBC of LA against spores were 0.315% and 40.375%, respectively, and the MIC and MBC of PAA against spores were 0.030% and 0.119%, respectively. Different concentrations of LA and PAA could decrease the spore germination rate, spore suspension turbidity, and spore hydrophobicity of B. cereus, and also increase the release of macromolecules in B. cereus spores, the content of spore reactive oxygen species (ROS), and the release of spore dipicolinic acid (2,6-pyridinedicarboxylic acid, DPA). The above results showed that LA and PAA could inactivate B. cereus spores by damaging the integrity of the cell membrane and cell wall of spores.